2016
DOI: 10.1680/jgein.15.00033
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory study on the use of EPS-block geofoam for embankment widening

Abstract: The use of expanded polystyrene geofoam (geofoam block) has been gaining momentum in roadway expansion projects. They are traditionally placed along the slope face of the existing roadway embankment as a side-hill fill. However, previous studies have shown the detrimental effects of seepage forces on the side-hill fill type of geofoam block configurations. In order to improve the performance of traditional embankment-widening configuration under seepage forces, an alternative geofoam block assembly is proposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 26 publications
0
3
0
1
Order By: Relevance
“…[16], [25]- [29], Akay [30], Özer ve diğ. [31]- [32], Özer [33] tarafından kullanılmış iki-boyutlu erozyon kanalı üçboyutlu hale getirilerek literatürde kullanılmamış kohezyonlu doğal topraktan oluşan bir şevin sızma suları altındaki davranışı boşluk-suyu basınç ölçümleri ışığı altında incelenmiştir.…”
Section: Sonunclassified
“…[16], [25]- [29], Akay [30], Özer ve diğ. [31]- [32], Özer [33] tarafından kullanılmış iki-boyutlu erozyon kanalı üçboyutlu hale getirilerek literatürde kullanılmamış kohezyonlu doğal topraktan oluşan bir şevin sızma suları altındaki davranışı boşluk-suyu basınç ölçümleri ışığı altında incelenmiştir.…”
Section: Sonunclassified
“…Field investigations [4], small centrifuge tests [5], and numerical analyses [6,7] have been conducted to analyze the deformation characteristics and mechanisms of widened embankments. As a result, geotextile reinforcements [8,9], geosynthetic clay liners [10], foundation columns [11], lightweight stacking materials [12,13], and combinations of these methods [14,15] have been proposed to solve problems that may occur in widened embankments.…”
Section: Introductionmentioning
confidence: 99%
“…Lu [21] proposed a maximum allowable differential settlement of 5.44 cm for an integrated pavement structure. Zhang [22] explored the reconstruction project of the Yan'an North Transit Line to analyze the differential settlement characteristics of the widened subgrade, the control standard of differential settlement for subgrade widening, and the rationality of wet and soft ground treatments via numerical simulation and field test According to Ozer [11], the structure of geofabric blocks can significantly improve the performance of traditional edge hill widening technology under seepage force. Phutthananon [12] found that the effect of soft soil layer thickness on differential settlement is not significant, but on average, settlement is significant; the effect of pile strength on differential settlement is significant only when the pile cap size is relatively small.…”
Section: Introductionmentioning
confidence: 99%